Strategi Peningkatan Keseimbangan Kehidupan Kerja Untuk Kesejahteraan Karyawan UMKM CV Jati Furniture Kemirahan Malang - Agung Suryo Prakoso; Madziatul Churiyah (Jurnal Manajemen Riset Inovasi, 2023)
The purpose of this study is to provide an overview for SMEs about the strengths, weaknesses, opportunities and threats that companies have in determining strategies and their implementation related to the Work-Life Balance Strategy at CV Jati Kemirahan Malang which is used as a policy basis in making decisions to increase employee welfare according to the strategy The selected. With a case study research design, researchers conducted research on CV Jati Kemirahan Malang. This research uses primary and secondary data, namely questionnaires and performance reports. Using SWOT analysis to determine strengths, weaknesses, opportunities and threats to determine the right strategy. From the results of the SWOT analysis, namely expansion, CV Jati Kemirahan Malang must innovate and develop to be able to maintain and improve employee welfare. To support the strategy that has been set, CV Jati Kemirahan Malang needs help from the government and employees' families.